2010
DOI: 10.1096/fj.10-170811
|View full text |Cite
|
Sign up to set email alerts
|

Structural insight into human variegate porphyria disease

Abstract: Human protoporphyrinogen IX oxidase (hPPO), a mitochondrial inner membrane protein, converts protoporphyrinogen IX to protoporphyrin IX in the heme biosynthetic pathway. Mutations in the hPPO gene cause the inherited human disease variegate porphyria (VP). In this study, we report the crystal structure of hPPO in complex with the coenzyme flavin adenine dinucleotide (FAD) and the inhibitor acifluorfen at a resolution of 1.9 Å. The structural and biochemical analyses revealed the molecular details of FAD and ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
87
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 59 publications
(90 citation statements)
references
References 47 publications
0
87
0
3
Order By: Relevance
“…In consequence, the mutations studied are most likely the cause of the reduced PPOX activities observed in patients carrying these defects. Moreover, Qin et al (2011) also found minimal or no residual activity for c.670T>G (p.W224G) and c.995G>C (p.G332A) mutations. No correlation was observed between these functional consequences and the expression or features of the disease in the patients carrying the respective mutations.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…In consequence, the mutations studied are most likely the cause of the reduced PPOX activities observed in patients carrying these defects. Moreover, Qin et al (2011) also found minimal or no residual activity for c.670T>G (p.W224G) and c.995G>C (p.G332A) mutations. No correlation was observed between these functional consequences and the expression or features of the disease in the patients carrying the respective mutations.…”
Section: Discussionmentioning
confidence: 90%
“…Three of these mutations c.101A>T (p.E34V), c.995G>C (p.G332A), and c.1265A>G (p.Y422C), affect amino acids highly conserved throughout evolution, whereas the mutations c.227C>T (p.S76F) and c.670T>G (p.W224G) change less conserved residues, but preserved in different mammals species such as Macaca fascicularis (monkey), Bos taurus (bovine), Sus scrofa (pig), Mus musculus (mouse), and Rattus novergicus (rat) (Protein Knowledgebase (UniProtKB), http://www.uniprot.org). In the crystal structure of human PPOX, amino acids E34, S76, W224, and Y422 are located in the FAD-binding domain, and G332 resides in the substrate-binding domain (Qin et al 2011). Besides, residues E34 and G332 are involved in the binding to cofactor and substrate, respectively (Qin et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations